Fatores associados à prevalência de enteroparasitoses em crianças de 0 a 4 anos do município de Patos de Minas, MG - Felício, Vanessa Pereira Tolentino (2007)
Helminths and intestinal protozooses still represent a worldwide health problem for man. The lack of systematic epidemiological studies of enteroparasitosis and the lack of notification contribute to the lack of information regarding the impact that these diseases have on the population. The objective of this study was to study the prevalence of intestinal parasitosis in children from daycare centers located in peripheral neighborhoods, in comparison with children from the community, of the same age group (0 to 4 years), belonging to the urban area in the city of Patos de Minas (MG). The study was carried out based on 356 results of parasitological examinations of children in that age group, with 100 children using municipal daycare centers and 256 children from the population treated at the University Laboratory of Clinical Analysis. Based on the results obtained, it can be concluded that: the general prevalence of enteroparasitosis in children was 34.0%. The risk index identified was 1.7 in daycare centers when compared to children in the community. There was a prevalence of 82.6% prevalence of protozoa in positive samples. The prevalence rates of protozoa were inversely proportional to the age group. The high rate of enteroparasites found in this study reflects a set of factors that have been neglected in many endemic countries. The results found show the need to improve sanitary conditions, basic sanitation and transmission control, in addition to implementing health education projects on the importance of hygiene habits and forms of transmission, aiming to interrupt the cycle established by such parasites.